Assessing the Nonbiodegradable Fraction of the Thickened Waste Activated Sludge. (1st August 2015) - Elbeshbishy, Elsayed; Dhar, Bipro Ranjan; Nakhla, George
ABSTRACT: : In this study, the feasibility of using three methods to estimate the nonbiodegradable fraction of five thickened waste activated sludge (TWAS) samples was evaluated using long‐term biochemical methane potential tests at four substrate to biomass ratios. The nonbiodegradable fraction was calculated based on the remaining volatile suspended solids (VSS), remaining total chemical oxygen demand (TCOD), and remaining total organic carbon (TOC). It was evident that the nonbiodegradable fraction of TWAS ranged from 12 to 27%. The average nonbiodegradable fractions of TWAS were 21, 18, and 23% based on remaining VSS, TCOD, and TOC, respectively. The proposed method can be potentially used to characterize biosolids for design and modeling anaerobic treatment processes.